Spatial and temporal links between shawinigan accretionary orogenesis and massif anorthosite intrusion, southern grenville province, New York, U.S.A. (September 2019) - Valentino, David W.; Chiarenzelli, Jeffrey R.; Regan, Sean P.
Highlights: Intrusion of the Marcy Anorthosite was immediately preceded by arc plutons in the Adirondacks during the Shawinigan Orogeny. A major shear zone follows the trace of an arc batholith defining a cryptic suture within the Adirondacks. The lithospheric-scale deformation zone, Piseco Lake shear zone, displays the hallmarks of transcurrent sinistral shear. The AMCG plutonism was triggered by slab detachment, and or delamination and rupturing of the lithospheric mantle. The AMCG suite is an important consequence of collisional processes that modified the Laurentian margin. Abstract: Synthesis of new and existing field, structural, geochemical, isotopic, and geochronologic data in the Adirondack Highlands of the southern Grenville Province indicate a suite of arc plutonic rocks (Piseco Lake granite suite) was intruded into basement rocks from ca. 1205–1180 Ma due to northward subduction beneath the Laurentian margin. Although rocks of similar age and origin are found in the Adirondack Lowlands and elsewhere in the Highlands, they occur in the greatest volume and are most intensely deformed in the Piseco Lake Shear Zone (PLSZ). This structure separates the Adirondack Highlands from ca. 1350-1300 Ma tonalitic gneisses in the southern Adirondacks. Tectonites in the PLSZ record the deformation of a continental arc batholith during collision with an outboard terrane which was accreted to Laurentia during the Shawinigan Orogeny. Internal to the PLSZ, a 10–15 km wide, subvertical zone of subhorizontally lineated L-S and L-tectonites (Piseco Lake gneisses) was derived primarily from megacrystic arc plutonic protoliths and documents sinistral relative motion. Intrusion of the arc granitoids, deformation and anatexis (ca. 1180–1160 Ma) throughout the entire Adirondack region immediately preceded and overlapped the intrusion of the anorthosite-mangerite-charnockite-granite (AMCG) suite at ca. 1165-1145 Ma in the Adirondack Highlands. We hypothesize that delamination or slab detachment, in combination with an irregular Laurentian margin, triggered disruption of the underlying lithosphere, allowed ascent of enriched asthenosphere, and facilitated the intrusion of voluminous AMCG rocks in the Adirondacks north of the PLSZ. Other large anorthosite massif complexes in the southern Grenville Province, including the Morin and Lac St. Jean bodies near the Laurentian margin, have also been linked to Shawinigan convergent structures and were an important part of accretionary processes documented in the Grenville Orogen.